DEVELOPMENT OF WORKLOAD ANALYSIS MODEL ACCORDING TO JOB MAPPING FOR HUMAN RESOURCES OPTIMALIZATION BASED ON EMPLOYEE’S COMPETENCIES AT BBPPMPV BMTI - Wanto, Wanto (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
All of employees at Vocational Education Quality Assurance Development Center from the Leadership to the Executor structure, work in accordance with the job mapping whose number and workload have been determined by the government. However, in daily tasks there are still employees who work overload and some are underloaded. So far, the workload of employees is determined by regulations which mostly calculate the employee's burden based on the physical workload, while the calculation of the workload based on the mental workload has barely been touched. The purpose of this study is to understand how to develop a workload analysis model according to job maps for optimizing human resources based on employee competencies. The formulation of the issue on this study is how to develop a workload analysis model according to the job map for optimizing human resources based on employee competencies. Analysis of the models is done by examining the existing workload analysis models, then making comparisons between each model, where the research step begins with a literature study and field observations. The development of the model is carried out by the following steps: determining the objectives or defining the problem, making a conceptual model, formulating the model, analyzing and the model solving, as well as the use of models. where the research step begins with a literature study and field observations. The development of the model is carried out by the following steps: determining the objectives or defining the problem, making a conceptual model, formulating the model, analyzing and the model solving, as well as the use of models. where the research step begins with a literature study and field observations. The development of the model is carried out by the following steps: determining the objectives or defining the problem, making a conceptual model, formulating the model, analyzing and the model solving, as well as the use of models.